2015
DOI: 10.5897/isaab-jhe2015.0017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the minerals, heavy metals and microbial compositions of drinking water from different sourcesin Utagba-Uno, Nigeria

Abstract: The presence of heavy metals in drinking water is of public health significance because of their toxicity at even low concentrations. Water should also be free of microorganisms.The quality of drinking water from tap, rain,river and bottled water within Utagba-Uno, a rural community in Ndokwa, Delta State was evaluated by determining the minerals, heavy metals and microbial compositions. The nine water samples analyzed included three bottled water samples (BW),tap water sample (TW), rain water sample (RW) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
(9 reference statements)
1
5
1
Order By: Relevance
“…This result is similar to the report of Kolawole and Obueh (2015) that isolated Staphylococcus spp., E. coli, Klebsiella, Salmonella and Pseudomonas spp. as heavy metals tolerant bacteria.…”
Section: Discussionsupporting
confidence: 83%
“…This result is similar to the report of Kolawole and Obueh (2015) that isolated Staphylococcus spp., E. coli, Klebsiella, Salmonella and Pseudomonas spp. as heavy metals tolerant bacteria.…”
Section: Discussionsupporting
confidence: 83%
“…But its more than the results founded by Kolawole and Obueh, ( 2015) who found that total heterotrophic bacteria co unts in tap water of Utagba-Uno, Nigeria was 1.2 × 10 2 CFU/ml.…”
contrasting
confidence: 41%
“…Many studies have been conducted in reference to the concentration and potential health risks associated with toxic metals, as well as necessary elements in surface, ground and bottled waters around the world (Hadiani, Dezfooli-manesh, Shoebi, Ziarati, & Khaneghah 2014;Kolawole & Obueh, 2015). However, there is limited data on both the chemical water quality monitoring and human health risk assessment (HHRA) of HM in drinking water in Uganda.…”
Section: Introductionmentioning
confidence: 99%